Kontribusi Strategi Belajar Mahasiswa dan Kualitas Pembelajaran Dosen Terhadap Prestasi Belajar Mata Kuliah Akuntansi Sektor Publik Mahasiswa Pendidikan Akuntansi Angkatan 2013 Universitas Muhammadiyah Surakarta - Pratiwi, Novia; , Prof. Dr. H. Yetty Sarjono, M.Si (2015)
Novia Pratama, A210110035, Accounting Education Program, the Faculty of Education, University of Muhammadiyah Surakarta, 2015 The purpose of this study was to: 1) To determine the contribution of the students' learning strategies on student achievement; 2) To determine the contribution of the quality of teaching faculty on student achievement; 3) To determine the contribution of student learning strategies and the quality of teaching faculty on student achievement. This research is a quantitative associative. The population in this study were all students of Accounting Education class of 2013 who took Public Sector Accounting courses totaling 184 students with a sample of 119 students were taken by proportional random sampling technique. Data obtained by using questionnaires and methods of documentation. Previous questionnaire has been tested and tested for validity and reliability. Data analysis technique used is multiple regression analysis, F test, t test, the relative contribution and effective contribution. Results from the analysis of data obtained by a linear line equation Y = 19,590 + 0,576X1 + 0,443X2. The conclusion that can be drawn from this research are: 1) no contribution to the achievement of student learning strategies learning courses Public Sector Accounting Accounting Education class of 2013. Student t test Berasarkan obtained t_hitung> t_tabel, namely 3.452> 1.981 (α = 5%) and value significance <0.05 is 0.001; 2) there is the contribution of the quality of faculty teaching courses on learning achievement Public Sector Accounting Accounting Education Student t test class of 2013. Based on the obtained t_hitung> t_tabel, namely 3,000> 1,981 (α = 5%) and a significance value <0.05 is 0.003; 3) there is the contribution of student learning strategies and the quality of faculty teaching courses on learning achievement Public Sector Accounting student class of 2013. Based Accounting Education hasi F test obtained F_hitung> F_tabel ie 14.394> 3.074 at 5% significance; 4) variable X1 relative contribution by 37% and the effective contribution of 13.7%, the variable X2 relative contribution of 7.6% and 6.2% effective contribution. The calculation result obtained R ^ 2 of 0.199, meaning 19.9% ​​achievement of students affected by the students' learning strategies and teaching quality of lecturers, the remaining balance of 80.1% is influenced by other variables not examined in this study. Keywords: student learning strategies, the quality of teaching faculty, academic achievement